A new contour reconstruction approach from dexel data in virtual sculpting - Yüksel, Kemal; Zhang, Weihan; Ridzalski, Boryslaw Iwo; Leu, Ming C. (IEEE COMPUTER SOC, 10662 LOS VAQUEROS CIRCLE, PO BOX 3014, LOS ALAMITOS, CA 90720-1264 USA, 2008)
This paper presents a novel method of contour reconstruction from dexel data solving the shape anomalies for the complex geometry in virtual sculpting. Grouping and traversing processes are developed to find connectivity between dexels along every two adjacent rays. After traveling through all the rays on one slice, sub-boundaries are connected into full boundaries which are desired contours. The complexity of the new method has been investigated and determined as O(n). We also demonstrate the ability of the described method for viewing a sculpted model from different directions.
Keywords: simulation; simülasyon